Scuttle Flies (Diptera: Phoridae) Inhabiting Rabbit Carcasses Confined to Plastic Waste Bins in Malaysia Include New Records and an Undescribed Species - Raja M. Zuha; See Huong-Wen; R. Henry L. Disney; Baharudin Omar (Tropical Life Sciences Research, 2017)
Scuttle flies (Diptera: Phoridae) are small-sized insects of forensic importance. They are well known for diversified species and habitats, but in the context of forensic entomology, scuttle flies’ inhabitance of corpses remains inadequately explored. With recent reports indicating the existence of more scuttle fly species possibly inhabiting these environments, a decomposition study using animal carcasses in enclosed environments was conducted. The aim was to record the occurrence of scuttle flies on rabbit carcasses placed in sealed plastic waste bins for a 40-day period. The study was conducted as two replicates in Bangi, Selangor. Sampling was carried out at different time intervals inside a modified mosquito net as a trap. Inside the trap, adult scuttle flies were aspirated and preserved in 70% ethanol. The fly larvae and pupae were reared until their adult stage to facilitate identification. From this study, six scuttle fly species were collected, i.e., Dahliphora sigmoides (Schmitz) ?, Gymnoptera simplex (Brues) ?, Megaselia scalaris (Loew) ??, Puliciphora borinquenensis (Wheeler) ?, Puliciphora obtecta Meijere ? and Spiniphora sp. ?. Both D. sigmoides and P. obtecta were newly recorded in Malaysia, whilst the Spiniphora sp. was considered an unknown species until it was linked to its male counterpart. The sealed waste bins were found to be accessible for the scuttle flies with delayed arrival (day 4–5). Megaselia scalaris was the primary scuttle fly species attracted to the carcass, and its occurrence could be observed between days 4–7 (replicate 1) and days 5–33 (replicate 2). This study also revealed Sarcophaga spp. (Diptera: Sarcophagidae) as the earliest species to colonize the remains and the longest to inhabit them (days 2–40). The larvae of Hermetia illucens (Linneaus) (Diptera: Stratiomyidae) and Fannia sp. (Diptera: Fanniidae) were found on the carcasses during the mid-advanced decay period. These findings expand the knowledge on the diversity of forensically important scuttle flies and coexisting dipterans in enclosed environments in Malaysia. Lalat mencalai (Diptera: Phoridae) ialah serangga kecil berkepentingan forensik. Ia amat terkenal dengan kepelbagaian spesies di habitat yang berlainan. Namun, dalam konteks entomologi forensik, kajian mengenai lalat mencalai yang dijumpai pada mayat masih kurang diberikan perhatian. Memandangkan terdapat pelbagai laporan yang menunjukkan kemungkinan terdapat kepelbagaian spesies lalat mencalai pada persekitaran mayat atau bangkai mereput, satu kajian pereputan bangkai haiwan di lokasi tertutup telah dijalankan. Kajian ini bertujuan merekodkan kehadiran lalat mencalai pada bangkai arnab yang diletakkan di dalam tong sampah selama 40 hari. Kajian ini dijalankan sebanyak dua replikasi di Tapak Simulasi Sains Forensik, Universiti Kebangsaan Malaysia, Bangi, Selangor. Persampelan lalat mencalai dilakukan mengikut selang masa berlainan di dalam kelambu yang diubahsuai. Di dalam kelambu tersebut, lalat yang terperangkap ditangkap dan diawet di dalam larutan etanol 70%. Larva dan pupa dipelihara sehingga peringkat dewasa untuk pengenalpastian spesies. Hasil kajian mendapati terdapat enam spesies lalat mencalai daripada bangkai, iaitu Dahliphora sigmoides Schmitz ?, Gymnoptera simplex (Brues) ?, Megaselia scalaris (Loew) ??, Puliciphora borinquenensis (Wheeler) ?, Puliciphora obtecta Meijere ? and Spiniphora sp. ?. Lalat D. sigmoides dan P. obtecta adalah rekod baharu di Malaysia manakala Spiniphora sp. adalah spesies yang belum dapat dikenal pasti sehingga ia dihubungkan dengan lalat jantannya. Lalat mencalai didapati berupaya memasuki tong sampah yang ditutup rapat (hari 4–5) dengan Megaselia scalaris sebagai lalat mencalai yang paling banyak ditemui pada bangkai pada hari 4–7 (replikasi pertama) dan hari 5–33 (replikasi kedua). Turut ditemui ialah Sarcophaga sp. (Diptera: Sacrophagidae) yang terawal tiba pada bangkai dan paling lama mendiami bangkai (hari 2–40). Larva Hermetia illucens Linneaus (Diptera: Stratiomyidae) dan Fannia sp. (Diptera: Fanniidae) pula dijumpai pada bangkai ketika tempoh pertengahan peringkat pereputan lanjut. Keputusan ini memperluaskan pengetahuan mengenai kepelbagaian spesies lalat mencalai berkepentingan forensik serta lain-lain lalat di persekitaran bangkai yang dilitupi di Malaysia.